Efficacy of the photon‐initiated photoacoustic streaming combined with different solutions on Enterococcus faecalis in the root canals. Issue 6 (16th February 2020) - Wen, Cheng; Kong, Yuanyuan; Zhao, Jian; Li, Yang; Yu, Miao; Zeng, Sujuan; Shi, Zhan; Jiang, Qianzhou
Abstract: This study aimed to evaluate the efficacy of different irrigation solutions used in photon‐initiated photoacoustic streaming (PIPS) or conventional needle irrigation (CNI) for eradication of Enterococcus faecalis from artificial root canals. Altogether, 240 artificial root canal samples were included. The models were split and incubated for 2 days to allow formation of E. faecalis biofilm. The models were randomly divided into two groups ( n = 120): CNI and laser‐activated irrigation (LAI). Each group was divided into six subgroups according to different irrigation solutions: distilled water, 1% sodium hypochlorite (NaOCl), 2% NaOCl, 5.25% NaOCl, MTAD, and chlorhexidine, respectively. After irrigation, half of the samples ( n = 10) were assessed immediately, and the other half of the samples ( n = 10) were incubated for 6 hr. Bacterial suspensions were obtained from all samples before and after irrigation, and after incubation, and were quantified adenosine 5′‐triphosphate (ATP) assay kit. The biofilms were examined using fluorescent microscopy and analyzed by Image Pro Plus software. Significant reduction of ATP, average fluorescence density after irrigation, and growth after incubation was obtained in LAI group than in CNI group ( p < .05). LAI can improve bacteriostasis effect of 2% NaOCl ( p < .05). PIPS improved the antibacterial effect of the 2% NaOCl used in root canal therapy. Abstract : Photon‐initiated photoacoustic streaming (PIPS) may improve the antibacterial ability of different irrigation solutions at the root canal. PIPS with 2% sodium hypochlorite (NaOCl) has improved capacity to eradicate Enterococcus faecalis planktonic bacteria and biofilm in the root canal.